FORMATION OF STUDENTS ' CULTURAL AND INTERROGICAL COMMUNICATION COMPETENCIES IIA LINGUISTICS (Innovative Technologica: Methodical Research Journal, 2022)
English: on the peculiarities of the selection of material and related texts in the development of the speech of future English teachers of the article.